2022
DOI: 10.1002/jmri.28156
|View full text |Cite
|
Sign up to set email alerts
|

Presurgical Magnetic Resonance Imaging Indicators of Revascularization Response in Adults With Moyamoya Vasculopathy

Abstract: Methods ParticipantsAll participants provided informed, written consent for this prospective, interventional study. All study components were 984Volume 56, No. 4

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…Prior work has shown that the CVR metrics are improved by surgical revascularization and can indicate good versus poor response to revascularization in adult moyamoya patients, as verified from neoangiogenesis on catheter angiography. 22,23 Our findings support this notion by showing that CVR metrics are less impaired in asymptomatic hemispheres in a much larger moyamoya cohort (n=73) and also provide evidence that the temporal parameters of the hemodynamic response function are the most sensitive to the presence of recent ischemic symptoms and have the highest predictive power for such symptoms. The exemplar statistics we show in Figure 5 complement recent reports of CVR ranges in healthy control volunteers.…”
Section: Discussionsupporting
confidence: 76%
“…Prior work has shown that the CVR metrics are improved by surgical revascularization and can indicate good versus poor response to revascularization in adult moyamoya patients, as verified from neoangiogenesis on catheter angiography. 22,23 Our findings support this notion by showing that CVR metrics are less impaired in asymptomatic hemispheres in a much larger moyamoya cohort (n=73) and also provide evidence that the temporal parameters of the hemodynamic response function are the most sensitive to the presence of recent ischemic symptoms and have the highest predictive power for such symptoms. The exemplar statistics we show in Figure 5 complement recent reports of CVR ranges in healthy control volunteers.…”
Section: Discussionsupporting
confidence: 76%
“…The aim of this procedure is to improve blood flow to the ischemic hemisphere through neoangiogenesis rather than simply bypass. 9,27,28 The improvement in blood flow is consistent with higher vascular density, improved perivascular pathways in the region of vascular growth, and ultimately reduced cortical ischemia. Consistent with these expectations, participants with prior surgical revascularization did not have a cortical reactivity dependency on the proximal arterial steno-occlusion, which is consistent with local angiogenesis improving the cortical reactivity in a manner that did not depend significantly on the more proximal arterial vasculopathy.…”
Section: Discussionmentioning
confidence: 72%
“…The indirect surgical EDAS procedure transposes a segment of the superficial temporal artery onto the surface of the brain to induce angiogenesis near the site of transposition. The aim of this procedure is to improve blood flow to the ischemic hemisphere through neoangiogenesis rather than simply bypass 9,27,28 . The improvement in blood flow is consistent with higher vascular density, improved perivascular pathways in the region of vascular growth, and ultimately reduced cortical ischemia.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In this issue of JMRI, Waddle et al offer a glimpse of the future with personalized revascularization decision-making strategy. 5 In a carefully designed and implemented prospective study, the authors propose a novel approach to predict the revascularization outcome for adult MMD with MRI-based evaluation of the posterior flow-territory reactivity. The analysis is motivated by the central hypothesis that as MMD preferentially affects the anterior circulation, the posterior circulation would display a compensatory increase in flow reactivity.…”
mentioning
confidence: 99%